TRADE IN SERVICES AND EMPLOYMENT: HARNESSING OPPORTUNITIES AND ADDRESSING CHALLENGES - GEORGETA ILIE (Global Economic Observer)
Considering the recent trends in international business, influenced by the new opportunities offered by increasing digitalization, as well as challenges generated by the post-pandemic economic and geopolitical pressures, this paper investigates the impact of recent developments in services and trade in services on employment. The starting point of this research is the statistical evidence highlighting the contribution of service activities to economic development and, implicitly, employment, as revealed by their high share in GDP and the labour market, globally. The paper is focused on the analysis of trade in services, with its particularities in terms of modes of supply and increased ability to use digital technologies, from the perspective of its capacity to create opportunities and also challenges on employment, depending on service industries as well as the level of development and market openness of countries. The research methodology combines a qualitative analysis of studies and empirical evidence in the field of services, trade in services and employment, accompanied by statistical data, covering the last three decades, available in the databases of international organizations. The main conclusion is that, despite the economic, geopolitical, technological or regulatory challenges, the strength of the services sector, due to the diversity of services, the dependence on services of all economic activities, the favourable service regulations, as well as the resilience of service industries in recent years, will continue to sustain the growth of trade in services and, implicitly, employment, thereby ensuring improvements in quality of life and economic development in all countries.